Curriculum Program Models for Embedding Character Values for Students - Syamsiah Syamsiah; Syamsuryani Eka Putri Atjo; Satriani Dahlan Hayyenah; Abdul Hafid; Rosmalah Rosmalah (Journal of Educational Science and Technology (EST), 2023)
The study aims: (1) to identify the character values for developing curricula programs, (2) to validate the content and design of curricular programs, and (3) to get the user target response on the curricular program for embedding character values to students. This developmental study involves some subjects, including educational experts, decision-makers, teachers, and students. Data were collected through interviews, documentation, and questionnaires. They were analyzed descriptively. The findings show that: (1) character values that should be included in curricular programs are: religiosity, politeness, courtesy, honesty, responsibility, forgiveness, patience, compassion, helpfulness, obedience, friendliness, diligence, cleanliness, tidiness, and discipline. (2) the tests on the content validity of curricular program design showed that it is very valid, and (3) assessments made by the target users on the curricular program are very good. Thus, the evaluation shows that the curricular program product is valid and practical. The findings could fulfill the demand for curricular programs for character education at Junior High Schools.